The analysis of the Soviet version of modernity in Johann Arnason’s historical sociology - M. V. Maslovsky (Социологический журнал, 2011)
In the article the formation of Johann Arnason’s sociology and its theoretical sources are considered. Peculiarities of Arnason’s approach to Soviet-type societies are singled out. The main aspects of his analysis of the Soviet model of modernity are characterized.